2018
DOI: 10.1161/circep.117.006107
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Left Anterior Oblique Projection

Abstract: BACKGROUND:Classical fluoroscopic criteria for the documentation of septal right ventricular (RV) lead positioning have poor accuracy. We sought to evaluate the individualized left anterior oblique (LAO) projection as a novel fluoroscopy criterion. METHODS:Consecutive patients undergoing pacemaker or defibrillator implantation were prospectively included. RV lead positioning was assessed by fluoroscopy using posteroanterior, right anterior oblique 30° to rule out coronary sinus positioning, and LAO 40° in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Individualized LAO is a refined method to improve the accuracy of fluoroscopy-guided RV septal lead placement. 10 The degree of individualized LAO is reported to be >60 degrees in the majority of patients (58%). 10 Therefore, LAO of 30°–40° can be insufficient to distinguish the septum from the free wall in most patients.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Individualized LAO is a refined method to improve the accuracy of fluoroscopy-guided RV septal lead placement. 10 The degree of individualized LAO is reported to be >60 degrees in the majority of patients (58%). 10 Therefore, LAO of 30°–40° can be insufficient to distinguish the septum from the free wall in most patients.…”
Section: Discussionmentioning
confidence: 94%
“… 10 Therefore, LAO of 30°–40° can be insufficient to distinguish the septum from the free wall in most patients. The need for the placement of a guidewire through the superior and inferior vena cava and a lead or catheter in the RV apex to calculate individualized LAO in this method 10 may lead to prolongation of procedure and fluoroscopic time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 The inferior margin can be considered as a line drawn from the superior tricuspid annulus (in whose superior end the His bundle is located) to the interventricular septum. 22 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] A recent report suggested that unexpected free wall pacing leads to increased occurrence of cardiovascular death and heart failure hospitalisation in patients undergoing RV septal pacing owing to AVB. 7 Recent reports showed that the use of individualised LAO 12 or right ventriculography 13 could improve the CT-judged accuracy of RV lead deployment on the RV septum by over 90%. However, determining the individualised LAO or performing right ventriculography during the procedure could prolong the procedural and fluoroscopic time.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%